2021
DOI: 10.3389/fmats.2021.723119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Tailings and Slag Powders on Workability and Mechanical Properties of Concrete

Abstract: Tailings are one of the largest solid wastes in stock at present. In order to improve the comprehensive utilization rate of tailings, especially to solve the problems of fine-grained tailings treatment, the concrete composite admixture was prepared by using iron tailings powder and slag powder. In order to study the influence of iron tailings powder on the workability and long-term mechanical properties of concrete, C30 and C50 concrete with different iron tailings powder dosages were prepared, and the slump, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Also, based on the TG curves of the three samples shown in Figure 12, it can be concluded that the contents of ettringite and C-(A)-S-H gels of C > D12 > D16 were 12.3%, 10.9%, and 9.9%, respectively, and the Ca(OH) 2 contents of C > D16 > D12 were 2.7%, 1.2%, and 1.1%, respectively. The content of carbonate of C > D12 > D16 was 7.3%, 2.4%, and 2.2%, respectively, which shows that the hydration product ettringite, C-S-H gel, and the change in calcium hydroxide content are the main factors causing the 28 d compressive strength of the SCMs [2].…”
Section: Hydration Products' Quantitative Analysis Test Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Also, based on the TG curves of the three samples shown in Figure 12, it can be concluded that the contents of ettringite and C-(A)-S-H gels of C > D12 > D16 were 12.3%, 10.9%, and 9.9%, respectively, and the Ca(OH) 2 contents of C > D16 > D12 were 2.7%, 1.2%, and 1.1%, respectively. The content of carbonate of C > D12 > D16 was 7.3%, 2.4%, and 2.2%, respectively, which shows that the hydration product ettringite, C-S-H gel, and the change in calcium hydroxide content are the main factors causing the 28 d compressive strength of the SCMs [2].…”
Section: Hydration Products' Quantitative Analysis Test Resultsmentioning
confidence: 87%
“…Iron tailings (IOTs) are waste residue with the dual characteristics of secondary resources and environmental pollution produced after ore dressing, which is the main component of industrial solid waste [1][2][3][4]. Data show that China's existing IOT stockpile has exceeded 5 billion tonnes, and the annual emissions of new IOTs are nearly 300 million tonnes, but the comprehensive utilisation rate of IOTs is only 27.69% [5].…”
Section: Introductionmentioning
confidence: 99%
“…The slump cone used in the test had a height of 300 mm, a top diameter of 100 and a bottom diameter of 200 mm. The detailed procedure for the slump test is descr as follows [22][23][24]: Initially, the necessary tools, including the concrete sample, a s slump cone, a metal rod, a trowel, scales, a measuring tape, and other equipment, w prepared. The concrete sample was prepared on-site and tested within 30 min of mix The concrete was poured into a clean, oil-free slump cone; filled to the top; and ge vibrated with a metal rod to remove air pockets and level the surface.…”
Section: Design Schemementioning
confidence: 99%
“…Wu et al (2021) [11] investigated concrete's workability and long-term mechanical qualities of iron ore tailings powder. The results of a study on the effects of increasing iron tailings powder doses on slump, expansion, flexural strength, splitting tensile strength, and compressive strength of concrete at different ages in C30 and C50 concrete revealed that iron tailing powder properly incorporated improves concrete's working performance and significantly reduces the time loss of fluidity.…”
Section: Introductionmentioning
confidence: 99%